Combined Blockade of Smad3 and JNK Pathways Ameliorates Progressive Fibrosis in Folic Acid Nephropathy - Jiang, Mengjie; Fan, Jinjin; Qu, Xinli; Li, Songhui; Nilsson, Susan K.; Sun, Yu Bo Yang; Chen, Yaping; Yu, Di; Liu, Dan; Liu, Bi-Cheng; Tang, Mingliang; Chen, Wei; et al. (Frontiers in Pharmacology, 2019)
Acute kidney injury leading to chronic kidney disease through tubulointerstitial fibrosis is a major challenge in nephropathy. Several signalling pathways promote interstitial fibrosis; however, effective suppression of fibrosis may require blockade of more than one pathway. This study investigated whether blockade of Smad3 and JNK signalling gives added suppression of interstitial fibrosis in folic acid nephropathy. A single high dose of folic acid (FA) causes acute tubular damage in C57BL/6J mice followed by interstitial fibrosis and chronic renal impairment. Co-activation of Smad3 and JNK signalling occur in both tubular epithelial cells and myofibroblasts in areas of tubulointerstitial damage and fibrosis in both murine FA-induced nephropathy and human IgA nephropathy. Groups of mice were treated with a Smad3 inhibitor (SIS3), a JNK inhibitor (SP600125), or a combination from day 6 after folic acid administration until being killed on day 28. Each drug efficiently inhibited its specific target (Smad3 phosphorylation or c–Jun phosphorylation) without affecting the other pathway. Given alone, each drug partially reduced renal fibrosis, whereas the combination therapy gave an additive and profound protection from renal fibrosis and improved renal function. Inhibition of Smad3 and/or JNK signalling activities prevented down-regulation of PGC-1α in tubular epithelial cells and up-regulation of PGC-1α in myofibroblasts during FA-induced renal fibrosis and inflammation. The expression of PGC-1α was upregulated in Smad3-/- NRK52E cells while downregulated in Smad3-/- NRK49F cells, suggesting that Smad3 signalling may regulate expression of PGC-1α in renal tubular epithelial cells and fibroblasts in distinct fashion. In vivo and cell culture studies also indicate that Smad3 and JNK signalling cooperate to cause mitochondrial dysfunction and cell damage in tubular epithelial cells via direct actions on the transcription of PGC-1α. These pathways also act cooperatively to promote renal fibroblast proliferation in tempo-spatial fashion. In conclusion, we have identified a potential combination therapy for progressive renal fibrosis which operates, in part, through modifying mitochondrial function.